2011
DOI: 10.1111/j.1524-4725.2011.02134.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Rejuvenation Using a Novel Bipolar Radiofrequency System in Asian Skin

Abstract: Fractional bipolar RF treatment is an effective treatment for facial photodamage in Asians, with a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Edema, bruising and pain can occur at the injection site, and adverse effects like ptosis, muscle weakness and headache have been reported [13]. Recently, an MFR device was developed, a novel and promising tool for facial rejuvenation [4]. Therefore, the aim of our study was to compare the effects of BoNT/A injection and MFR treatment on periorbital static wrinkles and lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Edema, bruising and pain can occur at the injection site, and adverse effects like ptosis, muscle weakness and headache have been reported [13]. Recently, an MFR device was developed, a novel and promising tool for facial rejuvenation [4]. Therefore, the aim of our study was to compare the effects of BoNT/A injection and MFR treatment on periorbital static wrinkles and lines.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [4] reported that PIH appeared in 40% (nonablative) and 92% (ablative) of patients who received fractional photothermolysis treatments. In our study, two patients (22.2%) reported PIH on the MFR treatment side which resolved spontaneously within 2 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent review of the literature postinflammatory hyperpigmentation (PIH) was observed in up to 40% and 92% of nonablative and ablative fractional laser-treated patients, respectively, 28 while in a retrospective study of 422 patients with SPT I-V, who received a combined total of 961 nonablative fractional laser treatments, the incidence was highest in patients with SPT V, occurring in association with 33% of treatments. 29 A study by Chan et al…”
Section: Laser Resurfacingmentioning
confidence: 99%